Caveat Blogger: Blogging and the Flight from Scholarship - Randy E. Barnett (Washington University Law Review, 2006)
While some law blogging is serious scholarship—and more could be serious scholarship than is now—almost all blogging, including most law blogging, is not serious scholarship and does not purport to be. Asserting that blogging is generally not a form of scholarship is no more an aspersion on blogging than is affirming that arguing in the Supreme Court is not scholarship. If undertaken by scholars, both activities can contribute constructively to one’s scholarship, and one might be a better advocate or blogger if one can draw upon one’s scholarly expertise. But it would be a mistake to confuse one of these activities with the other.
Keywords: Blogs; Law – Study & amp; teaching; Raich v. Gonzales 545 U.S. 1 (2005); Constitutional interpretation; Due process of law; Interstate commerce; Original intent (Law); United States